Utilization of Social Media as a Supporting Facility for Online Learning - Denisa Permata; Rina Maryanti (Universitas Pendidikan Indonesia (UPI), 2021)
The implementation of online learning in Indonesia is a new experience that also presents many challenges. This study aims to describe the implementation of online learning in Senior High School 2 in Kuningan and also the utilization of social media as a tool for supporting online learning. The method used in this research is descriptive qualitative method. The data sources are two teachers and ten students of Senior High School 2 in Kuningan. Data collection techniques were carried out using interviews and observations during online learning. The results of this study indicate that the utilization of social media can be a solution in overcoming the problems that arise as a result of the implementation of online learning. During online learning activities, Instagram is used as a means of teaching and learning activities. The use of Instagram social media in online learning provides a new experience in teaching and learning activities.